Twelve‐year outcomes of intestinal failure–associated liver disease in children with short‐bowel syndrome: 97% transplant‐free survival and 81% enteral autonomy. Issue 1 (8th June 2021) - Torres, Clarivet; Badalyan, Vahe; Mohan, Parvathi
Abstract: Our aim was to analyze the outcomes in children with short‐bowel syndrome (SBS), parenteral nutrition dependence (PND), and intestinal failure–associated liver disease (IFALD) treated in our Intestinal Rehabilitation Program (IRP) during 2007–2018. We retrospectively reviewed charts of 135 patients with SBS‐PND at the time of enrollment in IRP; of these, 89 (66%) had IFALD, defined as conjugated bilirubin (CB) of ≥2 mg/dl at enrollment and/or abnormal liver biopsy showing stage 2–4 fibrosis. Outcomes included resolution of CB, enteral autonomy, laboratory parameters (platelets, aspartate aminotransferase to platelet ratio index), growth trends, transplant rates, and mortality. Of the 89 patients, 74 had elevated CB at enrollment; the other 15 had normalized CB but had fibrosis on liver biopsy. Thirty‐eight patients had liver biopsies: 36 (95%) had fibrosis, including 21/36 with bridging fibrosis/cirrhosis. The median proportion of residual small bowel was 23% (interquartile range, 13%–38%) of the expected length for age and median, daily energy requirement by PN was 100%. Two received a transplant, three died (one posttransplant), and the remaining 85 survived; 69 (81%) achieved enteral autonomy. Seventy‐three (99%) of the 74 patients with hyperbilirubinemia normalized their CB with medical treatment. In a subset of eight of 89 patients with initial platelet count of <100, 000/μl(median 50, 500/μl) and median CB of 21 mg/dl, seven achieved CB normalization and had improved platelet count. Overall survival was 97% (censored 96.3%). We demonstrate high transplant‐free survival and enteral autonomy rates among children with SBS‐IFALD relying on low‐dose soybean lipid emulsion.